Distribution of Crop Yields in The Arid Regions of Rajasthan - Mruthyunjaya, Mruthyunjaya; Goyal, Doulat; Krishna, G V.S.R (Annals of Arid Zone, 2016)
Randomness, normality and year to year fluctuations in the yields of pearl millet and kharif pulses in western Rajasthan were studied using non-parametric tests, co-efficient of variation and probability of the crop yields as the tools of analysis. The analysis showed random distribution of yields, non - normal distribution in more than 50 per cent of the cases, very high probability of low yields and increasing tendency of fluctuations.